Design of an Internship Information System in the Information Systems Study Program at UIN Sulthan Thaha Saifuddin Jambi - Rezki Kurnia Sholehati Nala Putri; Hery Afriyadi; Bustomi Baharsyah (LKP KARYA PRIMA KURSUS, 2026)
Internships are a vital component of the curriculum in the Information Systems Study Program at UIN STS Jambi, aimed at providing students with real-world work experience. However, the management of internship-related information is still conducted manually, leading to issues such as delayed information delivery and data entry errors. This study aims to design and develop a web-based internship information system using the Waterfall development methodology and the CodeIgniter 4 (CI 4) framework as the main platform. The system includes features for managing student internship data, partner institutions, registration processes, and activity reporting. System testing was conducted through a feasibility questionnaire involving users, resulting in a score of 91.6%, indicating that the system is highly feasible for use in supporting internship administration processes. This system is expected to enhance the efficiency and accuracy of internship data management comprehensively. Keywords: Waterfall, CodeIgniter 4, Website, Internship, Feasibility Test